Exploration of human resources and tourism potential through POKDARWIS in pioneering a tourism village in Gemawang Village, Ngadirojo Sub-District, Wonogiri District - Widagdo, Yohanes Martono; Wibiyanto , Agung (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2024)
Tourism village pilot through the formation of POKDARWIS is an initiative that aims to develop tourism villages as attractive tourism destinations. This research aims to explore the potential of human and tourism resources through POKDARWIS activities in an effort to pioneer a Tourism Village in Gemawang Village, Ngadirojo Sub-district, Wonogiri Regency. This research uses descriptive qualitative. Data collection techniques with direct observation and interviews in a structured manner and literature study. The results showed that Gemawang Village has natural and cultural potential that can be developed into an attractive tourist destination. However, this potential has not been fully utilised due to the limited understanding of the community about their tourism potential. Through POKDARWIS activities, the community of Gemawang Village learnt to manage tourism potential sustainably and build close cooperation among residents to improve the attractiveness and quality of tourism services. This research provides new insights into the important role of human resources in local tourism development as well as the benefits of collaboration between the government, community, and other related parties in advancing the tourism sector at the village level.